KAI1 inhibits HGF-induced invasion of pancreatic cancer by sphingosine kinase activity - Liu, Xu; Guo, Xiao-Zhong; Zhang, Wei-Wei; Lu, Zhuo-Zhuang; Zhang, Qun-Wei; Duan, Hai-Feng; Wang, Li-Sheng (Hepatobiliary & pancreatic diseases international, 2011)
KAI1/CD82 has been reported to attenuate the process of metastases in a variety of tumors; however, its mechanism of action in invasion has not been fully elucidated. The present study aimed to investigate the importance of KAI1 in invasion and its correlation with activation of sphingosine kinase (SPK) in human pancreatic cancer PANC1 and Miapaca-2 cell lines. The expression of KAI1 in PANC1 and Miapaca-2 cells, which was mediated by recombinant adenovirus (Ad-KAI1), was assessed by a flow cytometer and Western blotting. After successful infection was established, in vitro growth curve and invasive ability in Boyden Chamber assay were studied. The presence of KAI1 correlating with c-Met and SPK was detected by co-immunoprecipitation and [γ- 32P] AT P incorporation. KAI1 genes had no significant effects on the curve representing cell growth. After infection with the KAI1 gene, decreased invasive ability in the Boyden Chamber assay was observed in PANC1 and Miapaca-2 cells that were induced by hepatocyte growth factor. Over-expression of KAI1 in the cells led to the deactivation of SPK and a decreased level of intracellular sphingosine-1-phosphate. No correlation was observed between c-Met and KAI1 during coimmunoprecipitation. The results of this study for the first time demonstrated a regulatory role for KAI1 in SPK activation, which leads to decreased invasive ability in disease progression of human pancreatic cancer.